Electric vehicles: a review of their components and technologies - Ahmed Abd El Baset Abd El Halim; Ehab Hassan Eid Bayoumi; Walid El-Khattam; Amr Mohamed Ibrahim (Institute of Advanced Engineering and Science, 2022)
The number of electrical vehicles (EVs) on the road has increased in recent years, including battery-electric vehicles (BEV), hybrid-electric vehicles (HEV), plug-in hybrid-electric vehicles (PHEVs), and fuel-cell electric vehicles (FCEV). This mode of transportation is expected to eventually replace internal combustion engine (ICE) vehicles, based on current trends. Each key EV component integrates several technologies that are either currently in use or have the potential to become prominent in the future. Environmental, power systems, and other industries may be adversely affected by electric vehicles (EVs). With sufficient EV penetration, the current power system could be subjected to severe instabilities; nevertheless, with proper management and coordination, EVs can significantly contribute to the success of the smart grid concept. Moreover, EVs have the potential to significantly cut transportation-related emissions of greenhouse gases. However, there are still considerable barriers that EVs must overcome before they can completely replace ICEs. The purpose of this study is to review all the relevant information available on EV architectures, battery energy sources, charging processes, and control approaches. Its goal is to provide a comprehensive overview of current EV technology.